Pengaruh Terapi Relaksasi Otot Progresif Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Curup - Wulan Dari Agustin; Darmawansyah Darmawansyah; Ice Rakizah Syafrie (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Background: According to data from the World Health Organization (WHO) in 2020, the prevalence of hypertension occurs in the adult age group of 25 years and older, at around 40%. Hypertension is predicted to cause about 7.5 million deaths, representing approximately 12.8% of global mortality. The WHO records that there are one billion people in the world suffering from hypertension, with two-thirds of them located in low-middle-income developing countries. The prevalence of hypertension is expected to continue to rise sharply, with estimates suggesting that by 2025, around 29% of adults worldwide will suffer from hypertension. Research Objective: This is to determine the Effect of Progressive Muscle Relaxation Therapy on Blood Pressure Reduction in Hypertensive Patients. Research Method: This research method is a quasi-experimental with a one-group pre-test and post-test design. The total sample used was 18 respondents, taken using a non-probability sampling method with purposive sampling technique. Statistical tests used a dependent T test on total cholesterol levels before and after the intervention. Research Results: The results of the univariate test analysis showed that among the 18 respondents, there were 10 males with a proportion of 58.8%, which is greater than that of females, with a standard deviation of 12.517. Females had an older average age (57.45 years) compared to males (44 years). The distribution of the respondents' education level was highest among those who had completed higher education, totaling 11 individuals (55%). Based on employment status, it was found that the majority were unemployed, totaling 12 individuals (60%). The results of the bivariate analysis yielded a significance value of 0.001 (p-value < 0.05), indicating an effect of relaxation therapy on patients with hypertension. Suggestions: The researcher hopes that this study can be used as a nursing intervention for complementary treatment in patients with hypertension.